Leitura de metáfora: derivando uma proposta de ensino - Evans, Débora (2018)
The reading performance of Brazilian students has long been far from ideal, so ensuring that the teaching of reading skills occurs in schools is a challenge for Brazilian education. Reading comprehensively, capturing even the implied messages is what is expected of a trained reader, so the perception of the implicit elements present in metaphorical relations, as well as the understanding of metaphors, are essential for comprehensive reading to occur. This work begins by presenting the positioning of linguistic semiology theorists, for whom the comprehension of metaphors would lead to the amplification of the reading ability followed by the Skinnerian interpretation about verbal behavior, reading and metaphor. Finally, from a behavioral analytical perspective, a teaching proposal is presented, highlighting aspects to be considered in the elaboration of a teaching procedure for the reading of metaphors, and its exemplification using a computerized platform. With such a proposal, it is hoped to contribute to the teaching of comprehensive reading